Meningkatkan Akuntabilitas Keuangan Daerah Melalui Penerapan Standar Akuntansi Pemerintahan Yang Efektif - Pashya niasty putri pasaribu; Hashifa Nuri; Muhammad Arsya; Mariana Mariana (EKALAYA : Jurnal Ekonomi Akuntansi, 2024)
This study aims to analyze the role of Leadership, Government Accounting Standards (SAP), and Public Participation in improving the accountability of regional financial management. The method used in this study is a literature review involving the collection and analysis of previous research related to the effective implementation of SAP and financial report transparency in the management of regional budgets. The results of the study indicate that leadership with integrity, the quality implementation of SAP, and active public participation play crucial roles in creating financial accountability at the regional level. Ethical leadership can promote accountability principles in financial management, while the effective implementation of SAP results in transparent and trustworthy financial reports. Furthermore, public participation in financial oversight increases government responsibility and strengthens the accountability system. Therefore, this study recommends reinforcing these three factors as strategic steps to achieve better and sustainable regional financial management.